Feasibility of prehabilitation for patients awaiting total knee arthroplasty; a pilot study - Mulder, Louisa T.M.A.; Berghmans, Danielle D.P.; Feczko, Peter Z.; de Bie, Rob A.; Lenssen, Antoine F. (Journal of orthopaedics, 2025)
To examine the feasibility of conducting a preoperative home-based prehabilitation program for total knee arthroplasty patients at risk for delayed in-hospital recovery, and to explore the pre- and postoperative impact of this program. A retrospective cohort study with matched controls, enabling subgroup analyses. Home-based. Patients awaiting primary unilateral total knee arthroplasty between 2019 and 2020, were compared with matched historic cases from 2016 to 2017. Matching criteria were scoring ≤17 points on the De Morton Mobility Index and >12.5 s on the timed-up-and-go test. Supervised home-based prehabilitation program versus no prehabilitation. Feasibility, determined by recruitment rate, adherence, and safety of the program. Preoperative impact, assessed for the intervention group by differences in mean values for aerobic capacity, muscle strength and functional mobility between the first and last sessions. Postoperative impact was defined as the time needed to achieve in-hospital independence of physical function and was measured by the differences in mean values between the intervention and control groups. Recruitment rate was 71 %; adherence and drop-out rates were 88 % and 12 % respectively. No adverse events were reported. Preoperatively, the intervention group showed significant improvements in aerobic capacity on the 2-min walking test (84.29 m–98.06 m; p = 0.007) and 2-min step test (40.35 steps to 52.95 steps; p = 0.014), muscle strength on the 30 s chair stand test (7.3 stands to 10.1 stands; p = 0.002), and functional mobility as seen in the timed-up-and-go-test (19.52 s–15.85 s; p = 0.031). Postoperatively, the intervention group achieved in-hospital independence of physical function earlier (mean rank 16.11) than the control group (mean rank 24.89; p=<0.01). It is feasible to conduct a prehabilitation program 4–6 weeks preoperatively, for high-risk patients awaiting total knee arthroplasty. Additionally, the program appears to have a positive impact on physical fitness both pre- and postoperatively.